2014
DOI: 10.1007/s13594-014-0181-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of raw milk produced by free-stall or tie-stall cattle herds in the Parmigiano-Reggiano cheese production area

Abstract: Tie-stalls used to be the common type of housing system for dairy cows in the Parmigiano-Reggiano cheese area; however, the proportion of free-stall herds has greatly increased over the last years. The aim of this study was to compare the milk characteristics between bulk tank milk produced in free-stall and tie-stall herds, in the Parmigiano-Reggiano cheese production area. Fourteen free stalls and 14 tie stalls were involved in the study. Bulk tank milk samples were collected monthly from each herd over a 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 27 publications
9
29
2
2
Order By: Relevance
“…The results for cheese fatty acid profile reflected the data already found for the corresponding milks (data not shown), confirming the differences in the fatty acid profile. These are not only due to the seasonal variation [47,48], but are closely linked to feed factors. In fact, various authors [30,49] have reported a complete transfer of FA from milk to cheese; hence, their profile largely reflected the raw milk from which they were made.…”
Section: Comparison Among Cheese Produced During Summer Seasonmentioning
confidence: 99%
“…The results for cheese fatty acid profile reflected the data already found for the corresponding milks (data not shown), confirming the differences in the fatty acid profile. These are not only due to the seasonal variation [47,48], but are closely linked to feed factors. In fact, various authors [30,49] have reported a complete transfer of FA from milk to cheese; hence, their profile largely reflected the raw milk from which they were made.…”
Section: Comparison Among Cheese Produced During Summer Seasonmentioning
confidence: 99%
“…During this period, the risk of milk not complying the legal limit that reaches the dairy transformation, does exist. Summer et al [6] reported that 10.71% of the samples collected from free stalls in the Parmigiano Reggiano production area (Italy), exceeded the legal limit of milk production from 2006 to 2008. This was confirmed by data of the Lombardia and Emilia Romagna Experimental Zootechnical Institute (IZSLER, Italy).…”
Section: Introductionmentioning
confidence: 99%
“…According to these results, about 10% of milk production in 2018 in these areas exceeded the 400,000 cells/mL limit [7]. These milks are mainly concentrated in the summer period [6], when the cows are subject to stress due to the hot and humid climate typical of the Po valley plain [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on milk technological characteristics have been carried out at individual cow level for phenotypic and genetic purposes. To our knowledge, only a few studies have investigated the variation of milk technological traits at bulk milk level using field data (De Marchi et al, 2007;Summer et al, 2014;Penasa et al, 2016), but those reports were based on small sample size or were conducted in a restricted geographical area. Milk quality payment system in Italy is mainly based on fat percentage, protein (or casein) percentage, SCC, and bacterial count, which derive from routine farm bulk milk recording.…”
Section: Introductionmentioning
confidence: 99%